Pengaruh Gaya Kepemimpinan, Disiplin Kerja Dan Kompensasi Terhadap Kinerja Karyawan Pada Hotel Bagus Jati Gianyar - Putra, Anak Agung Pramana; Widhiasthini, Ni Wayan (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2025)
This study aims to determine the effect of leadership style, work discipline and compensation on employee performance at Hotel Bagus Jati Gianyar. The population in this study were employees of Hotel Bagus Jati Gianyar, with a sample of 53 respondents. The method used was saturated sampling, where sampling used the entire population. The data analysis technique used was multiple linear regression analysis. Based on the results of the study, partially and simultaneously leadership style, work discipline and compensation have a positive and significant effect on employee performance at Hotel Bagus Jati Gianyar. The leaders of Hotel Bagus Jati Gianyar should be able to protect employees, improve employee discipline such as reprimanding employees who are late or employees who always ask for permission with unreasonable reasons, and it is also recommended to maintain employee work-life balance such as adjusting salaries or compensation according to working hours, job positions and government regulations.